Multispecies probiotics complex improves bile acids and gut microbiota metabolism status in an in vitro fermentation model - Liu, Wei; Li, Zhongxia; Ze, Xiaolei; Deng, Chaoming; Xu, Shunfu; Ye, Feng (Frontiers in Microbiology, 2024)
The consumption of probiotics has been extensively employed for the management or prevention of gastrointestinal disorders by modifying the gut microbiota and changing metabolites. Nevertheless, the probiotic-mediated regulation of host metabolism through the metabolism of bile acids (BAs) remains inadequately comprehended. The gut-liver axis has received more attention in recent years due to its association with BA metabolism. The objective of this research was to examine the changes in BAs and gut microbiota using an in vitro fermentation model. The metabolism and regulation of gut microbiota by commercial probiotics complex containing various species such as Lactobacillus, Bifidobacterium, and Streptococcus were investigated. The findings indicated that the probiotic strains had produced diverse metabolic profiles of BAs. The probiotics mixture demonstrated the greatest capacity for Bile salt hydrolase (BSH) deconjugation and 7α-dehydroxylation, leading to a significant elevation in the concentrations of Chenodeoxycholic acid, Deoxycholic acidcholic acid, and hyocholic acid in humans. In addition, the probiotic mixtures have the potential to regulate the microbiome of the human intestines, resulting in a reduction of isobutyric acid, isovaleric acid, hydrogen sulfide, and ammonia. The probiotics complex intervention group showed a significant increase in the quantities of Lactobacillus and Bifidobacterium strains, in comparison to the control group. Hence, the use of probiotics complex to alter gut bacteria and enhance the conversion of BAs could be a promising approach to mitigate metabolic disorders in individuals.